2020
DOI: 10.7731/kifse.3f6529d5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radiation Deterioration on Class 1E Cable Fire

Abstract: In this study, the effect of radiation deterioration on cable fire for a type of class 1E cable for a nuclear power plant was investigated. Combustion and smoke characteristics were compared via a cone calorimeter test (ISO 5660-1), and the toxicity index of the toxic gas emitted during combustion was analyzed by following the NES 713 standard. The peak heat release rate of the irradiated cable was measured to be approximately 38 kW/m<sup>2</sup> higher than that of the non-irradiated cable. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…In Figures 6(a) and 6(b) and 6(c), the second HRR exhibited a peak value in the section after 200 s, at least once during the three repetition tests in the non-aged cable and in the 90 and 100 °C-aged cables. Regarding this characteristic, previous studies [7,19] have reported that after the first PHRR, the flame retardant added to the cable sheath and insulation after the first PHRR forms a char layer on the cable surface and blocks heat penetration. They suggest that if the flame retardant performance decreases, the formation of the char layer becomes unstabe, which weakens its intensity, and after the flame retardant performance is maintained for a certain period, the second PHRR emerges, owing to the occurrence of cracks on the surface.…”
Section: Middle and Late Combustion Characteristicsmentioning
confidence: 98%
“…In Figures 6(a) and 6(b) and 6(c), the second HRR exhibited a peak value in the section after 200 s, at least once during the three repetition tests in the non-aged cable and in the 90 and 100 °C-aged cables. Regarding this characteristic, previous studies [7,19] have reported that after the first PHRR, the flame retardant added to the cable sheath and insulation after the first PHRR forms a char layer on the cable surface and blocks heat penetration. They suggest that if the flame retardant performance decreases, the formation of the char layer becomes unstabe, which weakens its intensity, and after the flame retardant performance is maintained for a certain period, the second PHRR emerges, owing to the occurrence of cracks on the surface.…”
Section: Middle and Late Combustion Characteristicsmentioning
confidence: 98%